EEG microstates dynamics of happiness and sadness during music listening - Ashish Gupta; Chandan Kumar Srivastava; Braj Bhushan; Laxmidhar Behera; Laxmidhar Behera (Frontiers in Human Neuroscience)
The human brain naturally responds to music, with happy music enhancing attention and sad music aiding emotion regulation. However, the specific electroencephalogram (EEG) microstates linked to these cognitive and emotional effects remain unclear. This study investigated the microstates associated with happiness and sadness, focusing on the alpha band, using classical music as stimuli. Results revealed a significant increase in class D microstate, associated with attention, during happy music listening. An inverse relationship between class C (linked to mind-wandering) and class D microstates was observed. Analysis of global explained variance (GEV) and global field potential (GFP) indicated that happy music upregulated class D and downregulated class C microstates compared to baseline. In contrast, sad music elicited an increased presence of class B, class C, and class D microstates, with GEV and GFP analyses showing upregulation of class C and class D compared to the resting state. These findings suggest distinct cognitive effects: (1) an increase in class D and reduction in class C microstates explain enhanced attention during happy music listening, and (2) the concurrent upregulation of class C and class D microstates underpins enhanced emotion regulation and self-regulatory goals observed upon sad music listening. Notably, compared to baseline, the mean microstate duration was significantly longer for both happy (p = 0.018) and sad (p = 0.0003) music, indicating that music listening enhances the temporal stability of active microstates. These findings advance the understanding of the neural mechanisms underpinning music's cognitive and emotional effects, providing a framework to explore music-induced changes in brain dynamics and their implications for emotion regulation and attentional modulation.